First report of the non-native snail Rumina decollata (Linnaeus, 1758) (Subulinidae: Gastropoda) in Córdoba (Argentina): implications for biodiversity and human health - Reyna, Paola Beatriz (2018)
Rumina decollata (Linnaeus 1758) is native to the Mediterranean region of Europe and north Africa. The first report in Argentina was in 1988 in Buenos Aires. In 2007, it was found in La Pampa and Mendoza. Here, we report its presence in Córdoba, extending its distributional range northwards more than 600 km. This finding is significant given that Rumina decollata is a facilitative predator and can deleteriously impact mollusk assembles causing ecological imbalances.